2011
DOI: 10.1021/bc200212a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drug Conjugation on Pharmacokinetics and Tissue Distribution of Anti-STEAP1 Antibody–Drug Conjugates in Rats

Abstract: Antibody-drug conjugates (ADCs) are designed to combine the exquisite specificity of antibodies to target tumor antigens with the cytotoxic potency of chemotherapeutic drugs. In addition to the general chemical stability of the linker, a thorough understanding of the relationship between ADC composition and biological disposition is necessary to ensure that the therapeutic window is not compromised by altered pharmacokinetics (PK), tissue distribution, and/or potential organ toxicity. The six-transmembrane epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
185
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(188 citation statements)
references
References 45 publications
3
185
0
Order By: Relevance
“…Pharmacokinetic parameters were calculated by noncompartment modeling, and also did not show significant differences in clearance rates for IgG-nAF and IgG at 0.31 ± 0.03 mL/h/kg and 0.3 ± 0.11 mL/h/kg, respectively (Table S2). Thus, our site-specific ADCs have pharmacokinetics similar to the unconjugated antibody, and improved relative to many nonspecifically conjugated ADCs (38,39). It is likely that nonspecific conjugates of hydrophobic drugs lead to a population of antibodies with reduced solubility.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Pharmacokinetic parameters were calculated by noncompartment modeling, and also did not show significant differences in clearance rates for IgG-nAF and IgG at 0.31 ± 0.03 mL/h/kg and 0.3 ± 0.11 mL/h/kg, respectively (Table S2). Thus, our site-specific ADCs have pharmacokinetics similar to the unconjugated antibody, and improved relative to many nonspecifically conjugated ADCs (38,39). It is likely that nonspecific conjugates of hydrophobic drugs lead to a population of antibodies with reduced solubility.…”
Section: Resultsmentioning
confidence: 93%
“…Next, we examined the pharmacokinetics of anti-Her2-IgG(HC-A121X)-nAF in rodents because most ADCs have reduced half-lives compared with the native antibody (20,38,39). A single dose of 1 mg/kg anti-Her2-IgG-nAF in PBS was injected intravenously in five rats, and serum was collected at regular intervals for 14 d and analyzed by ELISA using antihuman κ-antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-TENB2-MMAE was labeled with DOTA for 111 In complexation by random modification of lysine residues as previously described (19). We observed 2.9 and 3.1 DOTA units, respectively, by reduced and intact liquid chromatography mass spectrometry.…”
Section: Radiochemistrymentioning
confidence: 87%
“…Active immunization against STEAP1 using DNA prime/modified vaccinia virus Ankara boost strategy inhibits prostate cancer progression in a murine model [6]. The immunogenicity of STEAP1 has led to the development of anti-STEAP1 antibody-drug conjugates to combine the specificity of anti-STEAP1 antibody to the cytotoxic potency of chemotherapeutic drugs [37].…”
Section: Normalized Steap1 Protein Expression Was Significantly Corrementioning
confidence: 99%
“…STEAP1 overexpression could promote proliferation, invasiveness, tumorigenicity, and metastasis through ROS-levels upregulation in cancer. A recent study reported the interest of antibody-drug conjugates as promising therapeutic approach combining the STEAP1 antigen targeting specificity of monoclonal antibodies with the cytotoxic potency of chemotherapeutic drugs [37].…”
Section: Normalized Steap1 Protein Expression Was Significantly Corrementioning
confidence: 99%